HPV DNA Associates With Breast Cancer Malignancy and It Is Transferred to Breast Cancer Stromal Cells by Extracellular Vesicles - De Carolis, Sabrina; Storci, Gianluca; Ceccarelli, Claudio; Savini, Claudia; Gallucci, Lara; Sansone, Pasquale; Santini, Donatella; Seracchioli, Renato; Taffurelli, Mario; Fabbri, Francesco; Romani, Fabrizio; Compagnone, Gaetano; et al. (Frontiers in Oncology, 2019)
A causal link between Human Papillomavirus (HPV) and breast cancer (BC) remains controversial. In spite of this, the observation that HPV DNA is over-represented in the Triple Negative (TN) BC has been reported. Here we remark the high prevalence of HPV DNA (44.4%) in aggressive BC subtypes (TN and HER2+) in a population of 273 Italian women and we convey the presence of HPV DNA in the epithelial and stromal compartments by in situ hybridization. As previously reported, we also found that serum derived-extracellular vesicles (EVs) from BC affected patients contain HPV DNA. Interestingly, in one TNBC patient, the same HPV DNA type was detected in the serum-derived EVs, cervical and BC tissue samples. Then, we report that HPV DNA can be transferred by EVs to recipient BC stromal cells that show an activated phenotype (e.g. CD44, IL6 expression) and an enhanced capability to sustain mammospheres (MS) formation. These data suggest that HPV DNA vehiculated by EVs is a potential trigger for BC niche aggressiveness.